Adolescência e ato infracional: a família em conflito - Esmeraldo, Michelle Barrocas Soares (2011)
Numerous studies discuss the issue of adolescent in conflict with the law from the adolescent that committed infraction or from his perceptions. Taking into account the importance of the family in the life of all subject in development, this study sought the look of the families about the infraction of their adolescents under socio-educative measures. For this purpose, semi-open interviews were conducted with 20 families, ten of the boys and equal number of the girls. The institutions where the measures are applied in Natal / RN gave space for most family members to be interviewed. The data collected were arranged in tables and analyzed qualitatively following the socio-historical perspective. The survey revealed that the meanings attributed to the time of conflict with the law of the adolescents differ between the boys families and the girls . Most of the boys families see the infraction as a consequence of the influence of bad company, as a minor provocative of changes in the family s relations, left justified in a context marked by violence. Now for most part of the girls families, the infraction is seen as their responsibility, as generator of transformations within the family both emotional and economic , and inaugurates a search movement for conflicts resolutions. Through the testimonies of these families, it became evident that there was a family reality structured also by a conflicting social, economic and community context. Thus, before there is an infraction that demarcates the conflict in adolescence, there is a family in conflict.